Effects of topography on structuring local species assemblages in a Sri Lankan mixed dipterocarp forest. (27th November 2012) - Punchi‐Manage, Ruwan; Getzin, Stephan; Wiegand, Thorsten; Kanagaraj, Rajapandian; Savitri Gunatilleke, C. V.; Nimal Gunatilleke, I. A. U.; Wiegand, Kerstin; Huth, Andreas; Zuidema, Pieter
Summary One of the primary goals in community ecology is to determine the relative importance of processes and mechanisms that control biodiversity. Here, we examined habitat‐driven species assemblages and species distribution patterns as well as their temporal variations for three life stages of two censuses of a 25‐ha mixed dipterocarp forest at Sinharaja (Sri Lanka). Our general objective was to find out whether the species assemblages and associated habitat types changed with life stage, spatial scale and species attributes. We also analyse whether the habitat types were related to certain indicator species. Habitat types were determined with multivariate regression tree analyses driven by topographic variables. We found species assemblages associated with five distinct habitat types that appeared consistently for all life stages of the two censuses. These habitats were related to ridge‐valley gradients and a pronounced contrast in south‐west versus north‐east aspect. Habitat‐driven structuring was weak at the recruit stage but strong in the juvenile and adult stages. The species assemblage variance explained by topographic variables for different life stages ranged between 10% for recruits and 23% for juveniles. The species assemblages determined for different spatial scales (10, 20, 50 m) showed similar habitat partitioning, but the variance explained by the topographic variables increased in all life stages with spatial scale. This could be due to the homogenizing effect of topographic variables at the larger scales and unaccounted environmental variation at the smaller scales. The number of indicator species identified in the two censuses was higher in the juvenile stage than in the adult stage, and nearly all indicator species in the adult stage were also indicator species in the juvenile stage. Synthesis. Our study showed that approximately 75% of the variance in local species composition is unexplained. This may be due to spatially structured processes such as dispersal limitation, unaccounted biotic and abiotic environmental variables, and stochastic effects, but only 25% were due to topographic habitat association. Although the pronounced ridge‐valley gradient and contrast of south‐west versus north‐east aspect created consistent habitats, our results suggest that local species assemblages at Sinharaja forest are jointly shaped by neutral and niche processes.